Portable electrocardiograph for people with heart conditions (Ciencias de la Ingeniería y Aplicadas, 2021)
In recent years, heart diseases have progressively increased. Currently, medical monitoring equipment is aimed at portable systems which help prevent certain heart conditions and thus even death, thus leading to rigorous monitoring, analysis and remote control of vital signs, verifying whether these are within the parameters established by the doctor. The present work shows the design and construction of a portable system that integrates the acquisition of the electrocardiogram (ECG) signal in real time through a module that amplifies the signals to process them in a microcontroller, presenting its heart rate, and your information on an Oled screen, when processing the information and having any abnormality in the system, it will issue a text message through a GSM module to a family member or outpatient center with the possible illness and information about the patient to be promptly attended to, providing them with immediate support. . In addition, the device has a computer connection to monitor the heart rate and thus have a real-time image of the behavior of the heart. From the analysis it has been determined that the system has an effectiveness of around 90%.
Keywords: ECG; Portable System; Microcontroller; Monitoring